Porosity Engineering of MOF‐Based Materials for Electrochemical Energy Storage - Du, Ran; Wu, Yifan; Yang, Yuchen; Zhai, Tingting; Zhou, Tao; Shang, Qiyao; Zhu, Lihua; Shang, Congxiao; Guo, Zhengxiao (Advanced energy materials, 2021)
Metal–organic frameworks (MOFs) feature rich chemistry, ordered micro‐/mesoporous structure and uniformly distributed active sites, offering great scope for electrochemical energy storage (EES) applications. Given the particular importance of porosity for charge transport and catalysis, a critical assessment of its design, formation, and engineering is needed for the development and optimization of EES devices. Such efforts can be realized via the design of reticular chemistry, multiscale pore engineering, synthesis methodologies, and postsynthesis treatment, which remarkably expand the scope of applications. By imparting conductive backbones, guest compounds, and/or redox‐active centers, MOFs and their derivatives have been heavily explored for EES in the last decade. To improve the design of MOF‐based materials for EES, the strategies of pore architecturing of MOFs and their derivatives are systematically analyzed and their applications reviewed for supercapacitors and metal‐ion batteries. Potential challenges and future opportunities are also discussed to guide future development. Metal–organic frameworks (MOFs) and their derivatives have been extensively investigated for energy storage devices in the last decade. This overview examines structural and chemical components and coordination from the perspective of porosity, emphasizing the state‐of‐the‐art synthesis strategies and applications of MOFs in supercapacitors and metal‐ion batteries. Opportunities and challenges are highlighted for future development in the subject area.